Green Supply Chain Management Innovation in Promoting Sustainability in Indonesia's Palm Oil Industry - Danar Adityo Putro; Suharjito (Jurnal Penelitian Pendidikan IPA, 2025)
The palm oil industry is vital to Indonesia’s economy but faces regulatory, environmental, and cost challenges, driving the need for sustainable supply chains. This study examines the impact of Green Supply Chain Management (GSCM) on corporate sustainability performance and the mediating role of Green Innovation. It focuses on Green Procurement, Manufacturing, Logistics, and Packaging. This study a quantitative approach, data was collected from industry specialists through structured questionnaires. The research follows a structured process: problem identification, literature review, hypothesis development, data collection, and analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). PLS-SEM was chosen for its suitability in handling complex models, formative constructs, and non-normal data, making it ideal for predicting GSCM’s impact on CSP Data from 100 managers across more than 20 companies were analyzed using PLS-SEM with WarpPLS 6.0, which handles non-linear and complex relationships. Findings show GSCM significantly improves economic, environmental, and social sustainability, with Green Innovation mediating economic and social impacts but not environmental ones. The study underscores the need to align GSCM with SDGs for long-term sustainability and offers strategic insights for academics and practitioners.